2006
DOI: 10.1159/000098171
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes in Methicillin-Resistant <i>Staphylococcus aureus-</i>Colonized Neonates in the Neonatal Intensive Care Unit

Abstract: Background: Methicillin-resistent Staphylococcus aureus (MRSA) colonization can persist for prolonged periods, and patient-related factors are associated with persistent carriage in adults. However, such knowledge is lacking among neonates. Objectives: To better understand the outcome of MRSA-colonized neonates in the neonatal intensive care unit (NICU), we prospectively followed all colonized neonates until decolonization over 39 months and determined the incidence, duration of colonization, clinical outcomes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
1

Year Published

2008
2008
2025
2025

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 42 publications
(27 reference statements)
1
24
1
Order By: Relevance
“…In fact, there is a report that 10.4% of neonates in an NICU of Korea became usually colonized with MRSA and they could acquire MRSA colonization in a day (mean: 17days, range: 1-471 days). 16 However, in our study, the mean colonization rate of the conjunctiva and other parts of body were 53 and 48.5% at that time, respectively. This higher colonization rate might be a possible contributing factor for MRSA-associated bacterial keratitis development.…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…In fact, there is a report that 10.4% of neonates in an NICU of Korea became usually colonized with MRSA and they could acquire MRSA colonization in a day (mean: 17days, range: 1-471 days). 16 However, in our study, the mean colonization rate of the conjunctiva and other parts of body were 53 and 48.5% at that time, respectively. This higher colonization rate might be a possible contributing factor for MRSA-associated bacterial keratitis development.…”
Section: Discussioncontrasting
confidence: 61%
“…A significant percentage fails to decolonize before hospital discharge after 30 months. 16 Our present study demonstrated that healthy neonates who had been discharged from the nursery 2 days after birth also developed MRSA keratitis after discharge. Considering the fact that the colonization can be established even with 1 day of HCU stay, it is quite possible that healthy neonates with EKC are at a higher risk for the Table 2 Characteristics of the patients who showed bacterial keratitis associated with EKC Patient no.…”
Section: Discussionsupporting
confidence: 53%
“…Three of 18 eligible studies subgrouped their population into inborn and outborn and reported stratified data on 2726 inborns and 990 outborns. 31,38,41 Interestingly, the prevalence of MRSA colonization among outborn neonates was 5.8% (95% CI 1.9%-11.4%), compared with just 0.2% (95% CI 0.0%-0.9%) among inborn Time was from admission to screening, n was the evaluable sample. Data stratified by location (Europe, North America, Asia) and midyear of each study.…”
Section: Figurementioning
confidence: 97%
“…Eight studies provided data on the acquisition of MRSA during the ICU stay. 26,27,29,32,36,38,39,41 The acquisition rate was 4.1% (95% CI 1.2%-8.6%) among the neonatal and pediatric population, whereas among the neonatal population alone, 6.1% (95% CI 2.8%-10.6%) of patients acquired MRSA during the NICU stay. The pooled acquisition rate for the PICU population alone was not calculated because of insufficient data reporting (2 studies).…”
Section: Figurementioning
confidence: 98%
See 1 more Smart Citation